Liu Zijue and Whole-body Breathing Exercises on Elderly Patients with Chronic Obstructive Pulmonary Disease—A Comparative Study on Respiratory Function Improvement - Lijin DENG; Wenxia ZHANG; Jinxiu CHEN (康复学报)
Objective:To compare the effects of Liu Zijue and Whole-body breathing exercises on respiratory function in elderly patients with chronic obstructive pulmonary disease (COPD) and identify a better intervention protocol.Methods:A prospective randomized controlled trial was used. Sixty elderly patients with COPD on stable period were randomly divided into experimental group and control group, with 30 cases in each group. Both groups were given the same treatment and care. In addition, the experimental group was trained in Liu Zijue training, and the control group was trained in Whole-body breathing exercises. The training intensity was 1 time once a day, 30 minutes once a time, 5 days once a week, and continuous exercise for 12 weeks. The dyspnea symptoms, exercise ability and quality of life of both groups were evaluated and analyzed before and after training.Results:The MRC breathing difficulty score,6 minutes walk distance (6MWD),and SGRQ total score between the two groups had statistical significance before and after intervention (P<0.01).The differences after the intervention between the two groups were statistically significant (P<0.05).Conclusion:Compared with Whole-body breathing exercises, Liu Zijue is more conductive to improve the respiratory function of elderly patients with COPD, along with their activities and quality of life.